Needs Analysis of Oral Communicative Competence of Tour Guides The case of third year students at the Institute of Tourism (Algiers) - BEN REDDA Djamel (My University, 2011)
There is general observation that tour guides lack competence in oral performance in English. The sample of the students at the Institute of Tourism in Algiers shows a problem in oral communicative competence. Such a problem would push us to investigate about the real reasons behind it. The purpose of this study is therefore to examine the oral communicative competence needs of tour guidance students taking the example of the above mentioned institute. The objective is also to collect data in order to find out the sources of the problem, then to identify possible solutions to improve the oral communicative competence of the tour guides. To conduct this study, two instruments of data collection are used. First, a voice recording is used to analyse students’ oral communicative competence. In the light of the results of the interview, a questionnaire is designed. To analyse and discuss the findings in this study, a combination of two methods used; the needs analysis approach and the descriptive method. The voice recording and the questionnaire results show that the students at the institute of tourism are aware of the importance of English in their future professional career mainly speaking. The students show that they lack this skill because they do not have sessions of oral expression to make use of their English. Hence tour guides are in need of much time of classroom practice in oral and novel teaching techniques.